Improvement Of The Design Of The Saw-Cutting Machine - D. Madrahimov; A. Yuldashev; I. Mansurov (Zien Journals, 2024)
This article presents the schemes and the technological process of the pilon-cutting machine for cutting saws for gins and linters designed to simplify the design of the pilon-cutting machine and improve the accuracy of cutting saws
Keywords: Saw-cutting machine